Delocalization in Cr3+ luminescence of clinochlore: A pressure-induced transition from single-ion emission to pair emission. (October 2017) - O'Bannon, Earl; Williams, Quentin
Abstract: The luminescence spectra of Cr 3+ in (Mg, Fe 2+ )5 Al(Si3 Al)O10 (OH)8 -clinochlore, a layered silicate compound, are reported to pressures of ∼25 GPa at 298 K: our results encompass emission from single-ions, paired neighbors and vibronic lines. A transition from sharp single Cr 3+ ion (R-line) dominated emission to Cr-Cr pair (N-Line) dominated emission is observed under compression. Since Cr atoms are confined to a discrete layer within the structure, efficient Cr-Cr exchange only occurs within a single layer; the distance between the layers is too large for significant interlayer coupling to occur. This 2-dimensional, single-layer arrangement gives rise to three distinguishable Cr 3+ nearest neighbor pairs. Neighbor lines are assigned based on ferromagnetic coupling of these three emitting pairs. We observe a decrease in the separation between the split components of the R-line under compression, confirming that the Cr sites become less distorted up to at least ∼11.0 GPa. An increase in overlap between e g orbitals of neighboring Cr-ions (corresponding to delocalization of the excited state) under compression also likely occurs. The R-to N-line transition is fully reversible and hysteresis is not observed, indicating that this transition is purely electronic in nature. The intensity transfer between the single-ion and paired-ion emission changes with a ∼1/4th power law as a function of the Cr-Cr separation. Highlights: The Cr 3+ luminescence behavior of clinochlore has been investigated to 25 GPa. A transition from R-line to N-Line dominated emission is observed under compression. The transition is fully reversible and hysteresis is not observed. The intensity transfer between the single-ion and paired-ion emission changes with a ∼1/4th power law as a function of the Cr-Cr separation.